نماذج تعليم القواعد العربية للناطقين بغيرها - Safitri, Eli; Zahra, Fatimatuz; Norazizah, Siti; Maali, Abul (Jurusan Pendidikan Bahasa Arab, 2023)
Qawaid learning is one of the most important part in the methodology of learning Arabic. This paper examines the model of teaching Arabic grammar to non-native speakers. In order to know how the teaching process and what are the appropriate Arabic grammar teaching models for non-native speakers and also what solutions are being done so that the goals of teaching Arabic grammar can be achieved. This research is qualitative research with Miles and Huberman model analysis consisting of three flows, namely data reduction, data presentation and conclusions. The results of the study found that learning Arabic grammar for non-native speakers there are three models of education, namely the standard model, the inductive model and the modified model. Lack of interest in teaching Arabic grammar is one of the obstacles to achieving the education goals to be achieved.